The Effect Of Workload And Work Discipline On Work Productivity With Work Motivation As An Intervening Variable In Manufacturing Companies In Cikarang - Wachid Hasyim; Rustianah Rustianah; Riski Eko Ardianto; Lala Dahlia; Tri Wahju Wirjawan; Suryadi Suryadi (Utan Kayu Publishing, 2025)
The aim of this research is to determine the direct influence between workload and work discipline on work productivity and the indirect influence between workload and work discipline through work motivation on work productivity. This research uses quantitative methods with a population of 140 manufacturing company employees in Kalryalwaln, using a saturated sample. This research was processed using SmartPLS 3.2.9 data processing software and data collection was carried out via Google.